Theorizing university students’ engagement behavior in learning: a Faculty of Business and Management perspective / Siti Halijjah Shariff, Lennora Putit and Maliza Delima Kamarul Zaman - Shariff, Siti Halijjah; Putit, Lennora; Kamarul Zaman, Maliza Delima (Faculty of Business and Management, UiTM Shah Alam, 2020)
Engagement studies have been widely researched over the past decade. This theoretical paper highlights the need to examine influential factors such as students’ attitude, academics’ influence, and perceived control on knowledge and skills are affecting students’ engagement behavior in the learning developmental process. The study employs a quantitative research design by using quota-sampling technique. A total of 300 survey questionnaires are to be distributed to undergraduate students from the business and management faculty of a public university. Descriptive and inferential statistical procedures for data analysis would be carried out using both SPSS and Smart PLS-SEM statistical software. This study holds potential contribution towards generation of knowledge in understanding the psychological drives for learning engagement and its behavioral outcomes. By assuring active learning engagement amongst university students, it can attainably assist towards nation building of employable graduates who are knowledgeable, skillful, and resilient upon embracing the Industry Revolution 4.0.